Strategy to Increase the Number of Product Sales Using the Swot Method: Case Study in Solo Coffee Rates - Lucky Chrisaviano; Bekti Nugrahadi; Anita Oktaviana Trisna Devi (Comit: Communication, Information and Technology Journal, 2024)
Laju Kopi is a coffee shop centered in Yogyakarta and founded in 2018. They expanded at Solo in 2021. Laju Kopi Solo experienced a decline in sales because the company had not yet established an appropriate marketing strategy. This research aims to determine the strategy to increase product sales at Laju Kopi Solo using SWOT analysis. Research data collection used interview methods and distributed questionnaires to owners, employees, and consumers. This is to find out internal and external factors. After the value analysis of these factors, it can be identified that the Laju Kopi Solo is in quadrant I in the SWOT matrix. It shows that the Laju Kopi Solo is in a state of growth. Therefore, It can produce strategies that can increase product sales at Laju Kopi Solo.